(untitled) (Vietnam Journal of Community Medicine, 2026)
In the context of increasingly complex ophthalmic disease patterns, topical medications (eye drops, eye ointments) play a leading and essential role in outpatient treatment regimens. However, treatment effectiveness depends not only on the pharmacodynamics of the drug but also on the patient’s knowledge and safe compliance behavior. A lack of knowledge about the drug administration process – from checking the expiration date, techniques to avoid retrograde infection, to how to press the lacrimal punctum to reduce systemic side effects – can lead to treatment failure or cause serious complications such as mechanical corneal damage or superinfection. In reality, in Vietnam, the community’s awareness of ophthalmic drug safety is still limited; for example, a study at the Central Eye Hospital showed that up to 89.5% of patients did not know the components of the drugs they were using and 96.1% were unaware of the possible adverse effects. In particular, at the Outpatient Department of Facility 2D Nguyen Viet Xuan - Hanoi Eye Hospital, the group of patients covered by health insurance (BHYT) accounts for a large proportion, mostly elderly people and those with chronic diseases, who are vulnerable due to barriers to receiving information and the habit of self-medicating. Despite this, there is still a lack of specific research data on the current state of knowledge about safety when using eye drops among this particular group. Based on clinical practice and the role of nurses in health education, we conducted this study with two objectives: (1) To describe the general characteristics of outpatient BHYT patients and (2) To survey patients’ knowledge about safety when using eye drops, thereby providing a scientific basis for developing more effective counseling solutions.